Remote sensing change detection for ecological monitoring in United States protected areas. (February 2015) - Willis, Katherine S.
Highlights: Remote sensing change detection should be employed in ecological monitoring programs. Common applications monitored: land cover change, disturbance, phenology. Recommended data for monitoring landscape changes are Landsat, MODIS. Collaborations between ecologists, land managers, conservation groups are key. Data results should be reported in a relevant manner with open access. Abstract: Remote sensing allows for cost- and time-efficient monitoring of landscapes vital to the conservation of natural resources, ecosystems, and biodiversity. This review synthesizes and recommends best practice change detection methods for land management groups to monitor chief ecological change indicators currently monitored in United States protected areas. The indicators frequently monitored via change detection and reviewed here include: land use/land cover, disturbance, and phenology. Landsat data products are recommended for monitoring land use/land cover and disturbance, due to their continuous data accessibility free of cost since 1972. Data from the Moderate Resolution Imaging Spectrometer (MODIS) are recommended for monitoring changes in phenology due to its 1–2 day return interval at any given location. Best-practice remote sensing methods are stressed, such as careful validation of results, either by combination of remotely sensed datasets with high resolution imagery or in situ data, in order to increase accuracy and to better align the remotely sensed data to the scale of the on-the-ground processes. Reported results should always be presented with utmost clarity in a manner that is both applicable to managers and understood by the general public. Increased collaborations between ecologists, land managers, conservation groups, and scientists are compulsory for successful integration of remote sensing-based monitoring, which is vital for effective conservation in protected areas. Remote sensing change detection quantifies the effects of humans on a landscape scale without creating further disturbances to ecologically sensitive areas; the results of which can be used for efficient conservation management into the future.